Ensuring Equitable Work-Integrated Learning Opportunities for International Students - Andrew, Lesley (Journal of University Teaching and Learning Practice, 2020)
Ensuring equitable work-integrated learning (WIL) opportunities for international students can be problematic. This position paper explores this challenge within the context of the Master of Public Health course (MPH) in Australian universities. The availability and accessibility of placement and non-placement WIL for international students are examined through a desktop audit of MPH offerings across 27 public Australian universities. These findings, interpreted through the lens of cultural, social and financial capital suggest although international students stand to benefit more from WIL than their domestic peers, their opportunity to participate is lower. The paper argues a strength-based approach is needed to mitigate this issue of inequity. Suggestions are offered to improve equity in placement and non-placement WIL for international students.